Bowen disease of the nail unit: a retrospective study of 12 cases and their association with human papillomaviruses. (13th July 2016) - Perruchoud, D.L.; Varonier, C.; Haneke, E.; Hunger, R.E.; Beltraminelli, H.; Borradori, L.; Ehnis Pérez, A.
Abstract: Background: Bowen disease is the most frequent nail malignancy, usually seen as a verrucous plaque of the nail in men. Objective: To characterize the affected patient population, the clinical manifestations, the diagnostic delay and diagnostic steps, and presence of human papilloma virus (HPV) infection. Methods: We retrospectively evaluated all cases of Bowen disease of the nail unit over a period of 9 years. Data were obtained from our electronic database. Human papilloma virus genotype was assessed in biopsy specimens by polymerase chain reaction (PCR) sequencing. Results: We identified 12 cases of Bowen disease of the nail unit in 10 patients. Mean age at onset was 52 years, with a male predominance of 90%. The thumb and middle finger were the most frequently affected (66%). Fifty percent of the lesions presented as periungual and subungual verrucous tumours. Patients sought medical evaluation after a mean delay of 5.7 years; histopathological diagnosis was made after a mean delay of 3.2 years. HPV infection was identified in 75% of the cases. Conclusions: Any recently appeared verrucous lesion of the nail unit in men above the age of 40 years should raise the suspicion of Bowen disease and lead to further histopathological diagnostic procedures.